Setting up new services in the NHS : 'just add water!' - Norton, Kingsley (Community, culture, and change ;, 2006)
This guide for setting up a clinical service in the National Health Service is based on the author's experience of leading a nationally funded project to develop two new specialist services in different parts of the country and involving three separate NHS Trusts. The project successfully delivered two services for personality disordered patients based on the template of Henderson Hospital, a democratic therapeutic community (TC). Kingsley Norton takes the reader, step-by-step, through the entire process of setting up these new services. Unpacking Henderson Hospital's complex interpersonal env.